(untitled) (Research, Society and Development, 2021)
Objective: To investigate the practice of governance and technical management of pharmaceutical assistance in the municipality of Xinguara, Pará. Methods: This is a Case Study, which took place between July 2018 and June 2019, based on Action Research and the Triangulation of Methods, on the governance process and technical management of pharmaceutical assistance. Results: Evidence is presented on types of interventions that ensure a better quality of pharmaceutical assistance, the outcomes of the situational strategic planning workshop, compliance with indicators related to governance practices, indicators related to planning and management instruments, technical management of assistance pharmaceutical, clinical medicine management, sectoral policies and compliance with indicators related to pharmaceutical assistance logistics. Conclusion: It is inferred the need for municipal planning to make explicit the pharmaceutical assistance actions linked to the technical coordination of pharmaceutical assistance and linked to the management instruments. Pharmaceutical interventions are recommended to strengthen the governance and technical management of pharmaceutical assistance in the municipality of Xinguara, Pará.